2023
DOI: 10.1073/pnas.2200057120
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal delivery of full-length anti-Nogo-A antibody: A potential alternative route for therapeutic antibodies to central nervous system targets

Abstract: Antibody delivery to the CNS remains a huge hurdle for the clinical application of antibodies targeting a CNS antigen. The blood–brain barrier and blood–CSF barrier restrict access of therapeutic antibodies to their CNS targets in a major way. The very high amounts of therapeutic antibodies that are administered systemically in recent clinical trials to reach CNS targets are barely viable cost-wise for broad, routine applications. Though global CNS delivery of antibodies can be achieved by intrathecal applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 86 publications
2
9
0
Order By: Relevance
“…Moreover, intranasal delivery of insulin improved cognitive functions in AD patients and human subjects with amnestic mild cognitive impairment [ 29 ]. These findings support the feasibility of passive immunotherapy in AD via intranasal administration [ 28 , 29 ]. Nevertheless, there are still several disadvantages of intranasal administration.…”
Section: Introductionsupporting
confidence: 76%
“…Moreover, intranasal delivery of insulin improved cognitive functions in AD patients and human subjects with amnestic mild cognitive impairment [ 29 ]. These findings support the feasibility of passive immunotherapy in AD via intranasal administration [ 28 , 29 ]. Nevertheless, there are still several disadvantages of intranasal administration.…”
Section: Introductionsupporting
confidence: 76%
“…In contrast to previous studies, where large volumes of antibodies were applied in the whole nasal cavity [ 16 , 22 ], in the present study we used a more specific delivery mode by targeting the olfactory mucosa with relatively small volumes of antibody, and we followed antibody distribution in disease conditions. We observed that 11C7 administration onto the olfactory mucosa significantly reduces EAE-induced spinal cord motor symptoms and demyelination.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of intranasal 11C7 administration in chronic EAE is of particular interest for the development of new therapies for multiple sclerosis and CNS injuries such as stroke [ 22 ]. Indeed, the stabilization of neurological deficits in the chronic phase of EAE is due to permanent demyelination and axonal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Promising results have been reported in 1 study of anti-Nogo-A Ab treatment for acute SCI in humans, 56 and new advances have led to a noninvasive, intranasal delivery method for anti-Nogo-A Abs, which may greatly improve future clinical trials. 57 project was supported by the VA Polytrauma and Traumatic Brain Injury Rehabilitation Research Fellowship from the Department of Veterans Affairs, the Paul Kalmanovitz Central Nervous System Repair Research Program, NIH/NS115759, and the Department of Veterans Affairs.…”
Section: Discussionmentioning
confidence: 99%
“…Promising results have been reported in 1 study of anti-Nogo-A Ab treatment for acute SCI in humans, 56 and new advances have led to a non-invasive, intranasal delivery method for anti-Nogo-A Abs, which may greatly improve future clinical trials. 57…”
Section: Discussionmentioning
confidence: 99%